New trends in biogas production and utilization - Grangeiro, Luana Cardoso [UNESP]; Almeida, Sâmilla Gabriella Coêlho de [UNESP]; Mello, Bruna Sampaio de [UNESP]; Fuess, Lucas Tadeu; Sarti, Arnaldo [UNESP]; Dussán, Kelly J. [UNESP] (Elsevier, 2019)
Alternatives in biofuels today include three main sources of renewable energy derived from biomass: biodiesel, bioethanol, and biogas. Biofuels can be first generation (produced from food crops; using sugars, starches, and vegetable oils) or second generation (produced from all forms of lignocellulosic biomass) fuels. Renewable energy production from energy crops and agricultural or industrial waste or wastewater; for example, crops and agricultural residues, domestic wastewater, industrial wastewater, sewage sludge, and animal manure, is a viable solution because it provides the correct destination for various types of waste and facilitates energy production. This chapter presents an overview of biogas production, as well as applications for an efficient bioenergy recovery from anaerobic systems. Aspects regarding renewable energy sources, anaerobic processes, and biogas production, including some characteristics of biogas purification and upgrading, are presented. Overall, this text compiles critical information to better understand the potential of anaerobic biodigestion as a robust processing step for bioenergy production.
Keywords: Acidogenic; Biodigestion; Biohydrogen; Methane; Methanogenic